Direct Selling a Controversial Business Model: Recent Development and Future Research Agenda - Seow, Richard (Journal of Technology Management and Business, 2022)
Direct selling is one of the earliest distribution models that is currently used in the modern commercial world. Direct selling started as a business model and subsequently evolve to becoming a global phenomenon. There are extant scholarly efforts on this research theme in recent years. However, an effort to organise the literature on this theme is lacking. This paper aims to provide insights into the recent development and future research opportunities in direct selling. This paper conducts a systematic structured literature review on the scientistic discoveries in the past ten years. Research papers are carefully synthesised, compare, and contrasted to present a state-of-the-art understanding of the research topic. The reviews conducted in this paper were categorised into four different levels, namely industry level, direct selling organisations’ level, distributor level, and consumer level. This scholarly effort makes a significant contribution to the extant literature on direct selling.